Secure IoT communication in critical infrastructure using attribute based access control - Moritz Volkmann and Sascha Kaven and Kai Hendrik Wöhnert and Volker Skwarek (Bundesamt für Sicherheit in der Informationstechnik (BSI), 2024)
In this work, the authors combine the technologies of machine learning based intrusion detection, self sovereign identity, and attribute based access control to create a framework for the secure energy community of the future with active grid management and peer-to-peer flexibility trading.
Keywords: ABAC; IoT; SSI; Smart Grid